Effect of renin-angiotensin system inhibitors on survival rate of patients with breast cancer: systematic review and meta-analysis - Niloufar Naghibzadeh; Fereshteh Asgharzadeh; Majid Khazaei (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2020)
Introduction: Breast cancer is one of the most common cancers and the second leading cause of cancer deaths among women worldwide. There is direct relationship between hypertension and the risk of blood cancer. Since the studies have showed that renin-Angiotensin pathway can be involved in cancer progression, therefore, this study was performed with aim to investigate the effect of angiotensin-converting enzyme inhibitors (ACEI) on survival of breast cancer patients by meta-analysis method. Methods: In this systematic review and meta-analysis, the databases of pubmed, scopus, and web of science were systematically searched with the keywords of Breast cancer, neoplasm, tumor, Angiotensin receptor blockers, Angiotensin converting enzyme inhibitors and survival using OR and AND without a time limit until February 19, 2020. I2 index was used to assess the heterogeneity between the studies. Egger's test was used for assessment of publication bias. Data were analyzed by meta-analysis method using random effects model. Results: In this study, a total of 57708 papers were reviewed and 13 studies were included in this meta-analysis. The results of meta-Analysis showed that based on the random effects model, ACEI had no effect on the survival of patients with breast cancer (HR = 0.1; 95% CI: 12.1 to 0.89; p = 0.99). Conclusion: The results of the studies show that using angiotensin receptor blocker and renin-angiotensin system inhibitors had no effect on survival of patients with breast cancer.